2019
DOI: 10.1080/17445647.2019.1642248
|View full text |Cite
|
Sign up to set email alerts
|

Nitrate contamination risk of the Zagreb aquifer

Abstract: Nitrates present one of the main groundwater contaminants in the world and in the Zagreb aquifer. In order to reduce nitrate concentrations in groundwater, it is necessary to spatially define main nitrogen sources and areas which have the highest risk of nitrate contamination. This paper presents a map of nitrate contamination risk in the area of the Zagreb aquifer. It was constructed based on nine different layers that include natural characteristics and anthropogenic pressures. For the construction of the Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…The presence of the clayey cambic horizon, with a pedological profile structure of A-(B)w-C, is characteristic for the specified soil [31]. It has been shown that the thickness of the unsaturated zone varies from two meters in the southeastern part of the Zagreb aquifer to eight meters in the northwestern part [34], while in high waters, some areas can be flooded [35]. A great part of the unsaturated zone, especially in the left bank of the Sava River in the urban part of the City of Zagreb, has been disintegrated by anthropogenic influences, such as traffic, aerodeposition, industry, and illegal waste dumps.…”
Section: Study Areamentioning
confidence: 99%
“…The presence of the clayey cambic horizon, with a pedological profile structure of A-(B)w-C, is characteristic for the specified soil [31]. It has been shown that the thickness of the unsaturated zone varies from two meters in the southeastern part of the Zagreb aquifer to eight meters in the northwestern part [34], while in high waters, some areas can be flooded [35]. A great part of the unsaturated zone, especially in the left bank of the Sava River in the urban part of the City of Zagreb, has been disintegrated by anthropogenic influences, such as traffic, aerodeposition, industry, and illegal waste dumps.…”
Section: Study Areamentioning
confidence: 99%
“…The Zagreb aquifer, from a hydrogeological perspective, consists of three main units: an unsaturated part of the alluvial deposits (overburden), a shallow Holocene aquifer layer and a deeper Pleistocene aquifer layer. The unsaturated zone thickness varies from two to eight meters (Ružičić et al, 2012), while during high waters, some parts of the Zagreb aquifer area can be flooded (Huljek et al, 2019). However, it must be emphasized that a great part of the unsaturated zone is disintegrated by the anthropogenic influence, especially in the urban part of the City of Zagreb.…”
Section: Geological and Hydrogeological Settingsmentioning
confidence: 99%
“…Previous research on the Zagreb aquifer focused on hydrogeological interpretations and determining the connection between the geological structure and the Quaternary aquifer system of the Sava River in Croatia [3], determining the impact of Zagreb landfills on groundwater quality of the Zagreb aquifer [4], nitrate concentrations in groundwater and the potential impact of agriculture on groundwater quality [5][6][7], groundwater status and risk assessment for the River Basin Management Plans of the Republic of Croatia [1], interpretations of the content of stable isotopes [8,9], assessment of tritium released from the Krško nuclear power plant (Slovenia) as a groundwater tracer [10], and the reasons for falling groundwater levels in the Zagreb alluvial aquifer [11]. Mathematical modeling of the Zagreb aquifer was performed for the groundwater protection of the Zagreb aquifer [12] and pollution transport [13].…”
Section: Introductionmentioning
confidence: 99%